Detection of virulence to septoria tritici blotch (STB) resistance conferred by the winter wheat cultivar Cougar in the Irish Zymoseptoria tritici population and potential implications for STB control. (18th July 2021) - Kildea, Steven; Sheppard, Liam; Cucak, Mladen; Hutton, Fiona
Abstract: Septoria tritici blotch (STB) caused by the fungal pathogen Zymoseptoria tritici continues to be the most economically destructive disease of winter wheat throughout Ireland. Due to the widespread development of fungicide resistance in the Irish Z . tritici population, integrated strategies to control STB are increasingly necessary. A key component of such strategies will be the deployment of winter wheat cultivars with improved levels of STB resistance. Unfortunately, due to the nature of Z . tritici, such resistances are at risk of being overcome by the pathogen. In late summer 2020, foci of STB were observed across a range of winter wheat cultivars under evaluation for recommendation in Ireland. Common amongst these was the cultivar Cougar in each of their pedigree. To determine if the foci observed in 2020 resulted from strains virulent to Cougar, isolate collections were established and virulence screens conducted on Cougar and a range of the cultivars currently under evaluation. These confirmed the presence of Cougar‐virulent strains in the Irish Z . tritici population, and that this virulence affects not just Cougar, but also cultivars derived from it. Although the foci observed in 2020 were in both fungicide‐untreated and ‐treated plots, there was no evidence that these strains are more sensitive or resistant to fungicides compared to the wider Irish Z . tritici population, with moderate resistance to the SDHIs and azoles dominating. Combined, the present study confirms the need to ensure a diversity of control measures for STB, including ensuring a range of STB resistances are used. Abstract : Virulence to Cougar‐based septoria tritici blotch (STB) resistance has been confirmed in the Irish Zymoseptoria tritici population and impacts STB resistance in cultivars bred from Cougar.